STRATEGI JARINGAN PENGGIAT LITERASI DIGITAL DALAM KAMPANYE MELAWAN HOAKS PANDEMI COVID-19 - I Komang Agus Widiantara (Widya Sandhi, 2021)
The Ministry of Communication and Information (Kominfo) recorded and labeled 1,733 hoaxes related to Covid-19 and vaccines until May 2021. Mainstream media have not shown satisfactory results in educating the public in Indonesia in the midst of the infodemic. The Digital Literacy Activist Network (Japelidi) is one of the communities in Indonesia that has a great concentration on digital literacy. This community has a movement to educate the public who experience digital stuttering in the midst of the information wave of the Covid-19 pandemic. This article aims to explore the strategies used by Japelidi in mobilizing volunteers from various academics, communities to collaborations carried out during the Pandemic. The method used in. This study uses an analysis of the Culture Participatory Theory, which was initiated by Henry Jenkins. The findings are that Japelidi uses three clusters as a strategy in literacy development. This strategy consists of 3 circular clusters, namely the main cluster in the form of a single narrative, the meso cluster containing the description of the Single Narrative, and the outermost stakeholder cluster. While the digital literacy campaign strategies carried out are agenda setting, key message delivery, media distribution and target reach.